LITERATURE REVIEW PERBANDINGAN EFEKTIVITAS EKSTRAK TANAMAN KELOR (Moringa oleifera) DENGAN KETOKONAZOL DALAM MENGHAMBAT PERTUMBUHAN Candida sp. PADA Saboraud Dextrose Agar - Lidya Lyke Sonbait; Prisca Deviani Pakan; Idawati Trisno; Christina Olly Lada (Universitas Nusa Cendana, 2026)
Background: One of the fungi that often causes infectious diseases is Candida albicans with a worldwide prevalence of 66%. Candidiasis as a disease caused by Candida albicans infection can be found throughout the world and is able to attack all ages, both men and women. Purpose: To compare the effectiveness of Moringa oleifera plant extract with ketoconazole in inhibiting Candida sp. on Saboraud Dextrose Agar. Methods: The method of searching for article data sources is carried out through the Google Scholar and PubMed databases (2015-2020) to retrieve relevant articles published in English and Indonesian. Key terms and phrases related to the comparative effectiveness of Moringa oleifera, ketoconazole, Candida sp. growth, Saboraud Dextrose Agar used in the subject search. Results: Based on the results of a literature review from 23 journals consisting of comparative characteristics of the effectiveness of Moringa oleifera and ketoconazole plant extracts, 11 journals found that ketoconazole Moringa oleifera plant extract was more effective than ketoconazole, while 12 other journals said that ketoconazole was more effective. By doing a comparison between the two methods, it was found that ketoconazole was more effective to be used in inhibiting the growth of Candida sp. than Moringa oleifera plant extract. Conclusion: Based on 23 journals conducted by a literature review, it can be concluded that ketoconazole has better effectiveness in inhibiting the growth of Candida sp. than Moringa oleifera plant extract.